Analysis of Student Errors According to the Nolting Procedure on Mathematical Literacy Problems in View of Kolb's Divergent and Assimilation Styles - Luna Stefani; Liana Metta; Doni Azmi Roma (SHS Web of Conferences)
This study describes the types of student errors based on the Nolting procedure on mathematical literacy problems in the form of AKM questions in terms of Kolb's divergent and assimilation styles. This research uses descriptive qualitative type and has 28 subjects of class VIII students of SMP Negeri 10 Tanjungpinang. The data collection used were questionnaires, AKM questions and interviews. The use of data analysis techniques in this study includes reduction, data presentation and conclusion drawing. The findings of this study are that students with assimilation learning style type tend to make fewer mistakes than students with divergent learning style type. This finding shows that conceptual errors and application errors are the main obstacles for students in solving mathematical literacy problems, which are caused by limitations in understanding the problem and managing time effectively.